1982
DOI: 10.1021/ic00134a045
|View full text |Cite
|
Sign up to set email alerts
|

Formation and characterization of platinum(III)-ammonia complex ions using pulse radiolysis

Abstract: The reactions of hydroxyl radical with tetraammineplatinum( 11) perchlorate and of the hydrated electron with transdihydroxotetraammineplatinum(1V) perchlorate have been investigated in aqueous media with the fast-reaction technique of pulse radiolysis in conjunction with conductivity and UV-visible absorption detection. The kinetic studies have been supplemented by final-product analysis on pulse-irradiated solutions for the formation of free ammonia and for changes in the concentration of platinum(I1). The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…A plot of the ratio of the maximum absorption at pH 4.4 to the absorption values at lower pHs (2.75−3.9) vs the hydrogen ion concentration is linear. This behavior, which is analogous to those reported for platinum(III) ammonia and ethylenediamine complexes, , is consistent with the water-elimination process (eq 12) being in competition with protonation of the hydroxo ligand (eq 13) with the latter being responsible for the decrease in conductivity with increasing hydrogen ion concentration. The slope of the aforementioned plot gives the ratio of k 13 / k 12 as 840 M -1 .…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…A plot of the ratio of the maximum absorption at pH 4.4 to the absorption values at lower pHs (2.75−3.9) vs the hydrogen ion concentration is linear. This behavior, which is analogous to those reported for platinum(III) ammonia and ethylenediamine complexes, , is consistent with the water-elimination process (eq 12) being in competition with protonation of the hydroxo ligand (eq 13) with the latter being responsible for the decrease in conductivity with increasing hydrogen ion concentration. The slope of the aforementioned plot gives the ratio of k 13 / k 12 as 840 M -1 .…”
Section: Resultssupporting
confidence: 87%
“…Reaction of e a q - with trans -[Pt(cyclam)(Cl) 2 ] 2+ . Studies of the reactions of e aq - with other platinum(IV) complexes have shown that these processes occur very rapidly by electron transfer. , The reaction of the platinum(IV)−cyclam complex is given by eq 5 for argon-saturated solutions at pH 4.0 to 10.7. Sufficient tert -butyl alcohol ( t -BuOH) was added (0.042−0.21 M) to scavenge hydroxyl radical (eq 4) but not H-atom although the latter is a minor component (20% relative to e aq - ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inc.) (l3), and the compound was characterized by comparison of its uv absorption spectrum with that reported (14) and by elemental analysis (15). All solutions used for pulse radiolysis experiments, carried out at about 23"C, were prepared just prior to use with triply distilled water or water purified by a Millipore Super-Q system.…”
Section: Experimenbl Sectionmentioning
confidence: 99%